Association of parvovirus B19 and myocarditis/dilated cardiomyopathy: A systematic review and meta-analysis. (January 2022) - Khatami, Alireza; Razizadeh, Mohammad Hossein; Ghadirali, Monire; Yazdani, Shahrooz; Bahadory, Saeed; Soleimani, Alireza
Abstract: Background: The potential association between Parvovirus B19 and heart disease has been controversial. The aim of the present study was to report the prevalence of B19 in myocarditis and dilated cardiomyopathy (DCM) as well as measure the statistical association between them. Methods: Our systematic search was carried out to retrieve published articles between January 2000 and March 2021 using three major databases: PubMed, Scopus, and Web of Science, as well as the Google Scholar search engine. The overall prevalence of HAV, pooled odds ratio, and heterogeneity were estimated by comprehensive meta-analysis (V2.2, Biostat) software. Results: The overall prevalence results in myocarditis and DCM were 23.7% (95% CI: 18.7%–29.5%) and 34.1% (95% CI: 23.8%–46.1%) respectively; in addition, the overall OR for B19 and myocarditis was 4.317 (95% CI, 1.831–10.180) versus 1.163 (95% CI: 0.706–1.916) for B19 and DCM. Conclusion: Our findings have shown a significant association between Parvovirus B19 and myocarditis with a high prevalence. In the case of DCM, no significant association was found while the prevalence of the virus was relatively high. Highlights: Viral infections, especially B19 virus, have been reported in people with cardiac complications (myocarditis and DCM). The prevalence of B19 virus in myocarditis was 23.7% (95% CI: 18.7%–29.5%) and in DCM patients was 34.1% (95% CI: 23.8%–46.1%). A statistically significant association was found between the prevalence of the virus and myocarditis (OR: 4.317, 95% CI: 1.831–10.180; P = 0.001), but in the case of DCM, the association was not significant (OR: 1.163, 95% CI: 0.706–1.916; p < 0.553). Presumably, B19 viral infection can be considered as a potential risk factor for myocarditis; however, more studies are needed in this area.